“Growing through relationship” - the Engagement of the Health Professional Students in the Internship Experience: a Grounded Theory Research - Merlini , Cinzia; Savarese, Mariarosaria; Pierboni, Lara; Mazzocchi , Barbara; Benedetti, Tiziana; La Sala, Rachele; Boggian , Alessio; Rinieri , Maria Teresa; Sarli, Leopoldo; Artioli , Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim:Little is known about the students’ engagement in the training experience and how it is lived by the health professional students. We aim at building a theoretical model of the engagement process starting from their lived experiences with Grounded Theory approach.Methods:In-depth qualitative interviews are conducted with 12 students from the Master Degree Courses in Nursing, Physiotherapy and Prevention Techniques in the environment and in the workplace, who had carried out and/or were doing internships in the same territory (2nd and 3rd year).Results The health professions' student engagement in the training program is developed in three main phases: initial phase, central phase and final phase, where emotions, behaviours, awareness contribute to the development of the entire engagement process with different relevance. The intertwining of these different components that develop along the stages of the experience gives life to the core category: growing through relationship, which expressed the crucial role of the relational network built during the internship experience in shaping students’ engagement.Conclusions: The results of this study underline the crucial role of students’ engagement in the internship experience in favouring both better learning outcomes and perspective professional success and wellbeing. (www.actabiomedica.it)